Determinants of Household Food Waste in Varanasi: A Socio-Behavioural Analysis (Indian Journal of Social Science and Literature (IJSSL), 2025)
Food waste is an increasingly critical issue, particularly in urban households, where it intersects with concerns of food security, environmental sustainability, and public health. In Varanasi, India, a densely populated and culturally diverse city, household food waste presents a unique challenge due to varying socio-economic conditions and traditional food practices. This study focuses on the role of women in managing household food, aiming to understand the types and quantity of food wasted and the socio-behavioural factors contributing to this issue. It further explores how targeted educational interventions can help reduce food waste. The primary objective is to analyse patterns of food waste in Varanasi households and investigate the socio-economic and dietary factors influencing waste generation. Additionally, the study evaluates the effectiveness of educational interventions in reducing food waste and fostering behavioural change. To assess the pre- and post-KABP (Knowledge, Attitudes, Beliefs, and Practices) on food waste among the women in the households (HH) 2. To measure food waste in households. To educate the women of the household on the interconnection between food waste, climate change, food insecurity, and malnutrition. The study involved women aged 18 to 49, including those who were pregnant or lactating, from diverse socioeconomic backgrounds. The Kuppuswamy socio-economic scale was used to classify participants, while a structured KABP questionnaire was administered both before and after the intervention. Food waste was measured over three consecutive days using labelled trash bags provided to each household. Participants were then provided with practical information on portion control, reuse of leftovers, and sustainable food practices through handouts and discussions. The Statistical Package for the Social Sciences (SPSS) was used to analyse changes in behaviour and food waste patterns before and after the intervention. The study found an average household food waste of 1 kg per day in Varanasi, with lower-middle-class households generating the most due to poor food management. Following the intervention, food waste decreased by 20%, with over 80% of participants showing a decrease improvement in portion control and the reuse of leftovers. However, behavioural changes related to meal planning and composting remained limited, indicating a need for ongoing support and infrastructure development. Socio-economic status emerged as a significant determinant of food waste patterns. Educational interventions effectively increased awareness and reduced food waste by approximately 20%, underscoring the importance of communitybased efforts. Socio-economic challenges and infrastructural limitations remain barriers. Scalable policies and sustained educational campaigns are necessary for the broader adoption of sustainable practices.